Production and functional characterization of tick salivary protease inhibitors - Kotál, Jan (Jihočeská univerzita, 2014)
Two cysteine and two serine protease inhibitors from a tick Ixodes ricinus saliva were overexpressed using a prokaryotic overexpression system and refolded to their native state. Both cysteine protease inhibitors were tested as potential antigens for an anti-tick vaccine showing no effect on tick feeding or reproduction. Various immunological methods were employed to test the potential immunomodulatory function of these proteins without success.
Production and functional characterization of tick salivary protease inhibitors
Keywords: tick; ixodes; ricinus; refolding; saliva; vaccine